Reconfiguration of palliative oncological nursing care: nursing contributions - Carolina Fraga Paiva; Tânia Cristina Franco Santos; Hercília Regina do Amaral Montenegro; Ricardo da Costa; Gizele da Conceição Soares Martins; Antonio José de Almeida Filho (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze the strategies implemented by nurses to reconfigure palliative oncological care due to the hospital accreditation process in Hospital do Câncer IV (Hospital of Cancer IV). Method: qualitative research of historical-social approach, whose direct sources in use were written documents and four spoken accounts. Results: implemented strategies were: creation of the Nursing Division; nursing staff management; consolidation of Continuing Education sector; creation of Internal Nursing Bylaws through development of norms and routines; meetings; discussion of clinical cases; training and classes; creation of Núcleo de Assistência de Enfermagem (Nursing Assistance Core); creation of a tumoral and ostomy wound-dressing ambulatory; and organization of the 5th Vital Sign Forum. Final considerations: nurses, supported by an alliance with the institution directors, implemented effective strategies and reached significant advancement. As they took part in this endeavor, they became legitimate spokespeople of an authorized discourse in the field of oncological nursing care in Brazil.